The primary psychiatric conditions: Clinical characteristics - Smitha S Prabhu; Shivam Goyal (Wolters Kluwer Medknow Publications, 2023)
Primary psychiatric conditions are those conditions, wherein the cutaneous manifestations are secondary to functional psychopathology in the brain. These comprise of psychiatric disorders with dermatologic manifestations and include conditions such as dermatitis artefacta, delusions of parasitosis, obsessive-compulsive disorders, body-focused repetitive behavior disorders, or somatoform disorders. Herein, we describe the clinical features and diagnostic methods of the individual primary psychiatric conditions, most of which have definitive diagnostic criteria in Diagnostic and Statistical Manual of Mental Disorders, and discuss the differential diagnoses encountered in clinical practice, in brief.